1990
DOI: 10.1016/0014-5793(90)80120-8
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐activity relationship in vasoconstrictor effects of sarafotoxins andendothelin‐1

Abstract: Sarafotoxins (SRTa, SRTb and SRTc) as well as endothelin-1 (ET-l) produced vasoconstrictions in rat thoracic aorta, rat isolated perfused mesentery and pithed rat in various of extents. The potency was ET-l > SRTb > SRTa > SRTc at lower doses, but SRTb > ET-I > SRTa > SRTc at higher doses. [Nitrophenylsulfenylated Tt@r]SRTb and SRTb(l-19) caused no vasoconstriction. Either the reduction and carboxymethylation of Cys residues, the destruction of the intramolecular loop or the production of the non-natural disul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…37 for the vasoconstrictor activity of endothelin in porcine coronary artery strips (ETa). 44 ET [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] has been shown to be inactive,45 while the hydrophobic C-terminal hexapeptide ET [16][17][18][19][20][21] has been reported to be a partial agonist in guinea pig isolated bronchus, rat vas deferens, and rabbit pulmonary artery.46•47 Structure-activity studies of the C-terminal hexapeptide of ET-1 have indicated the importance of individual amino acids to receptor recognition in a variety of tissue beds.48•49 However, we have found that this fragment is devoid of functional activity in several tissue preparations including rat aorta and rabbit pulmonary artery. 49 Other studies attempting to demonstrate the agonist activity originally reported for the ET [16][17][18][19][20][21] fragment have likewise met with little suc- The peptides prepared by Boc chemistry were deprotected and cleaved from the resin using anhydrous liquid HF/ anisóle or HF/p-cresol (9:1 v/v) followed by N-terminal acetylation with 90% acetic acid and an excess of acetic anhydride.…”
Section: Introductionmentioning
confidence: 99%
“…37 for the vasoconstrictor activity of endothelin in porcine coronary artery strips (ETa). 44 ET [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] has been shown to be inactive,45 while the hydrophobic C-terminal hexapeptide ET [16][17][18][19][20][21] has been reported to be a partial agonist in guinea pig isolated bronchus, rat vas deferens, and rabbit pulmonary artery.46•47 Structure-activity studies of the C-terminal hexapeptide of ET-1 have indicated the importance of individual amino acids to receptor recognition in a variety of tissue beds.48•49 However, we have found that this fragment is devoid of functional activity in several tissue preparations including rat aorta and rabbit pulmonary artery. 49 Other studies attempting to demonstrate the agonist activity originally reported for the ET [16][17][18][19][20][21] fragment have likewise met with little suc- The peptides prepared by Boc chemistry were deprotected and cleaved from the resin using anhydrous liquid HF/ anisóle or HF/p-cresol (9:1 v/v) followed by N-terminal acetylation with 90% acetic acid and an excess of acetic anhydride.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the amino acid sequences of sarafotoxins, found in the venom of the burrowing snake Atractaspis engaddensis, are very similar to those of endothelins (Kloog & Sokolovsky, 1989). All the endothelins and sarafotoxins are bioactive but differences exist in their pharmacological potencies and profiles (Kitazumi et al, 1990;Cardell et al, 1992). Two distinct receptor subtypes for endothelins, namely ETA (Arai et al, 1990) and ETB (Sakurai et al, 1990) have been cloned and biochemically characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Sarafotoxins (SRTs), having chemical structures similar to those of ETs, also consist of a novel cardiotoxic peptide family [2] and these peptides interact witla ET receptors [1]. A diverse set of pharmacological activities with different potencies exerted by ET/SRT family peptides [3][4][5][6] suggested the existence of ET/SRT receptor subtypes. We have reported that two distinct subclasses of ET receptors, namely, ET-l-specific and ET/SRT family-common receptors, are distributed in various proportions in human and porcine tissues [7].…”
Section: Introductionmentioning
confidence: 99%